2017
DOI: 10.1021/acs.orglett.7b01463
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of (±)-Rhodonoids C, D, E, F, and G and Ranhuadujuanine B

Abstract: Here we describe the divergent, biosynthetically inspired syntheses of (±)-rhodonoids C-G and (±)-ranhuadujuanine B. The key steps of the syntheses include the construction of the chromene unit through a formal oxa-[3 + 3] annulation and a biomimetic acid-catalyzed ring cyclization. Cationic [2 + 2] cycloaddition is accomplished to form the cyclobutane core of (±)-rhodonoids E and F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…As expected, this ligand provided the highest enantioselectivity of the series (ee's up to 87 %, entry 46). Finally, we also found that replacement of a thioether moiety by a selenoether group had little effect on enantioselectivity (e. g. entries 1, 6 and 7 vs [49][50][51].…”
Section: Synthesis Of Ir and Rh-catalysts Precursorsmentioning
confidence: 69%
See 1 more Smart Citation
“…As expected, this ligand provided the highest enantioselectivity of the series (ee's up to 87 %, entry 46). Finally, we also found that replacement of a thioether moiety by a selenoether group had little effect on enantioselectivity (e. g. entries 1, 6 and 7 vs [49][50][51].…”
Section: Synthesis Of Ir and Rh-catalysts Precursorsmentioning
confidence: 69%
“…Ligands L1 a,f,g, L11 a,f,g, L12 g, L14 g and L18 f,g and complexes [Rh(cod)(L14 g)]BF 4 and [Ir (cod)(L14 g)]BAr F were synthesized as previously reported. [14] Substrates S1, [40] S2, [41] S5, [42] S6-S7, [43] S8, [44] S9, [45] S10-S11, [46] S12-S14, [47] S17-S23, [10g] S24, [48] S25, [49] S26, [10b] S31, [50] S33-S38, [51] S39- Table 9. Selected asymmetric hydrogenation of α-aryl enamides S40-S46 with Rh-L15 g catalytic system.…”
Section: Methodsmentioning
confidence: 99%
“…BDP-OH was synthesized as described in the literature (Scheme S1 †). 20,21 The synthetic route of aza-BODIPY derivatives is depicted in Fig. 1a.…”
Section: Resultsmentioning
confidence: 99%
“…Some other studies about Taiji have also been conducted in Refs. [36][37][38]. Nevertheless, the forecast for the capability of Taiji in the future cosmological parameter estimation has never been seriously studied.…”
Section: Introductionmentioning
confidence: 99%